KINERJA SOSIAL INDUSTRI KECIL AGRO DI PRIANGAN TIMUR - Charina, Anne; Kusumo, Rani Andriani Budi; Mukti, Gema Wibawa (Universitas Galuh, 2023)
In line with increasing global pressure to contribute to a sustainable world, many contemporary businesses are starting to express awareness of social practices in their business. This study aims to explore social performance in agricultural small industry in East Priangan. Using a qualitative approach, data was collected by interviewing 20 agricultural small industry owners who carry out social practices in their business. Thematic analysis with N-vivo version 12 software was used to analyze the data obtained. This study reveals that normative values and Islamic values are the basic motives behind the social performance of small agro industries. Types of social performance carried out by small agro industries include: involving the community in business, providing social and health security for employees, participating in business associations/networks and providing routine compensation to the community.